Neuropathic spinal arthropathy leading to spine disruption, spinal cord transection, and aortic displacement: brief case report. (December 2018) - Goetz, Lance; McAvoy, Sean; Zakrzewski, Kate
Abstract Introduction Charcot spinal arthropathy (CSA) is an infrequent but potentially devastating complication after spinal cord injury. Case presentation We report a case of a man with longstanding T3 complete (AIS A) paraplegia who developed severe CSA with spine disruption and aortic displacement. Discussion Acute management of this patient is described along with both conservative and surgical management considerations and challenges as described in other reports.